Literasi baca tulis pemuda Sumberkerto - M, Nur Akbar Erwinsyah; Putra, Fandi Rahmanta; Indriwardhani, Sri Prameswari (2021)
basic meaning of literacy is abillity to read and write. Not all the youth in Sumberkerto village in Malang have a privelage to learn or study in higher education, The problem that was raised in this research is their ability in writing a literary work in the form of a creative short story with the level of education they have taken. The subjects were several youths in Sumberkerto Village with various backgrounds of education. Creative writing can be interpreted as an activity to flow creative ideas that are buried in someone's mind and become a written work, which one is a short story. The method used in this research is observation and the provision of materials or assistance. The result of this research with providing material using Powerpoint showed that most of the participants understood the material that had been delivered, but only a few of them were able to produce good creative short story according to the presented material.